Mengukur Kemajuan Desa: Profil Desa Tanjung Batu Sebagai Indikator Pembangunan Lokal - Astuti, Winda; Rusmayani, Sri; Sadikin, M. Nur Atdeni (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2024)
This article aims to measure village progress using the village profile as an indicator of local development. Village development is an effort or series of efforts carried out consciously by a village for planned growth and change towards modernity. The essence of development is to build society as a whole, in order to achieve people's welfare. Therefore an effective tool is needed to measure their progress. A village profile is a tool used to comprehensively describe the characteristics and conditions of a village. This article will discuss how village profiles can be used as indicators of local development by identifying various key factors that reflect economic, social and environmental development in villages.In this article, we will discuss data collection for village profiles, including information about education, health, facilities and infrastructure, livelihoods of village residents, as well as environmental aspects such as environmental sustainability, sustainability of natural resources and human resources. In addition, we will also discuss how this data can be analyzed and used to measure village progress over time. By using village profiles as indicators of local development, we can ensure that available resources are used efficiently to improve the quality of life of village residents and encourage sustainable economic growth.